Dental caries among a group of boys with β-thalassemia major (10-12 years old) in relation to salivary Mutans streptococci - Raghad R Al-Zaidi; Sulafa K El- Samarrai (College of Dentistry/ University of Baghdad, 2014)
Background: Beta thalassemia major is an inherited disorder that may affect general and oral health.The purpose of this study was toassess the severity of dental caries in relation to oral cleanliness, mutans streptococciamong a group of boys with beta thalassemia majorin comparison with a control group. Materials and Methods: The study involved 30 boys with BTM aged 10-12 years compared to 30 healthy boys with the same age group. d1-4mfs and D1-4 MFS indices were applied (Muhlemann, 1976), the viable counts of mutans streptococci in stimulated saliva were also determined. Results: The entire thalassemic group was caries-active. For both dentitions, a higher dmfs/DMFS values were recorded for study compared to control group, difference was statistically not significantconcerning dmfs, while it was statistically significant concerning DMFS (P